STILL’S DISEASE IN A DULTS (CLINICAL CASES) - M. Z. Kanevskaya; T. B. Kondratyeva (Klinicist)
Objective: to analyse and describe clinical cases of Still’s disease in adults and peculiarities of therapy in patient with a monocyclic course of the disease who had at the beginning of the observation a high systemic account (12) and in patient with a recurrent course of the disease with a positive result for 25 and 10 years of a dynamic observation.Materials and methods. Patient L., a female, 35 years old, was taken to the therapeutic department of the clinic with fever of 38–39 °С, chills and sweating, resistant not itching rash, lymphadenopathy, signs of myocarditis, loss of 20 kg of weight, exudative pleurisy, pronounced orthopnea with respiration rate of 40–48, tachycardia up to 130 beats per minute, myalgia, hepatosplenomegaly and abdominal pains. In past medical history for 2 months of the disease the patient was examined, and the sings of disease progression were present. The clinical constellation in patient L. allowed us to formulate a diagnosis of Still»s disease. Some investigations were conducted repeatedly to track the changes. The following therapy by Indomethacin in a daily dose of 150–200 mg/day for 1 year and for 6 months in combination with D-penicillamine in a dose of 450 mg/day induced remission. Till the end of 2016 the disease recurrence was not revealed. In another patient B., a male of 57 years old, the disease manifested with sub-febrile temperature, pain in a testicular area, thrombocytosis, and the symptoms increased in 2 weeks and included resistant febrile temperature, lymphadenopathy, changes of laboratory tests, signs of nephropathy and encephalitis. The patient was examined to exclude oncology.Results. Still’s disease was diagnosed and the following therapy was administrated: diclofenac and methotrexate for 4 years with episodes of disease recurrence in case of decreasing the doses of the medications, but in future the therapy managed to cancel, and there was no recurrence observed.Conclusion. These clinical cases have demonstrated peculiarities of course, diagnostic and management of patients with Still’s disease, the possibility of prescribing non-steroidal anti-inflammatory drugs and synthetic basic anti-inflammatory drugs for achievement of persistent disease remission.